Rare case of infratemporal fossa mucocele after facial fracture - Dayang Suhana, Binti Abang Madzhi; Salina, Binti Hussain (Pakistan Medical Association Rawalpindi Islamabad Branch, 2012)
We present a rare case of an infratemporal fossa mucocele in a 55 year old man with history of previous midfacial fracture. Patient presented with history of right infraorbital swelling and ectropion with normal vision. The computerized tomography scans confirmed a cystic lesion occupying the right infratemporal fossa extending to the right infraorbital region. The mucocele was successfully excised via right translabial approach.